Del heroísmo hacia el ensueño: en torno a las “Páginas cervantinas” de Darío en los alrededores culturales del 98 - Valero Juan, Eva Mª (Anales de Literatura Hispanoamericana, 2008)
Commencing with “The pages of Cervantes” published by Jorge Eduardo Arellano in 2002 titled Don Quijote cannot and must not die, the article deals with Ruben Dario’s “quijotism” or “cervantism” with regards to his view of Spain, in the ideological context of the change of century; a period in which the ideals related to Quijote of 98’s intellectuals permit us to go further in the relationship between Spain and Latin America at the dawn of the Twentieth Century.